Cheese and milk quality of F1 Holstein x Zebu cows fed different levels of banana peel - Melo, Marco Túlio Parrela de; Rocha Júnior, Vicente Ribeiro; Caldeira, Luciana Albuquerque; Pimentel, Paulo Roberto Silveira; Reis, Sidnei Tavares dos; Jesus, Diego Lucas Soares de (Acta Scientiarum. Animal Sciences, 2017)
This study aimed to evaluate the effects of the inclusion of different levels of sun-dried banana peel in the diet for crossbred cows on the quality of Minas fresh cheese and milk. Diets consisted of 0, 15, 30, 45 and 60% replacement of sorghum silage with banana peel. Ten cows were assigned to two 5 x 5 Latin squares experimental design. Milk samples were taken from each cow and analyzed for composition. Milk was pasteurized for the production of Minas fresh cheese, which was weighed to determine the yield and analyzed for texture, physical and chemical characteristics and consumer acceptance test. Milk urea nitrogen had a quadratic effect with minimum point at 43.76% replacement of silage with banana peel. The remaining items evaluated in the composition of milk and cheese and the consumer acceptance test were not influenced by diets with banana peel. The replacement of up to 60% sorghum silage with banana peel is a viable alternative because it causes no alteration in physical and chemical composition of milk and Minas fresh cheese, as well as consumer acceptance.